Fishing Techniques by Fishermen in Pohon Batu Village, Waesama District, South Buru Regency - Taipabu, Jania; Riry, Roberth Berthy; Leuwol, Ferdinand Salomo (Jurnal Pendidikan Geografi Unpatti, 2024)
With its vast marine resource potential, Indonesia has a strategic fisheries sector needs development. However, most fishermen still live in poverty. Maintaining sustainable marine resources is crucial for a sustainable economy. Many factors, including catch and economic conditions, influence fishermen's income. In Maluku, the fisheries sector plays a vital role in the local economy, although there are challenges in increasing fishermen's income. Sustainable management and access to capital and technology are needed to improve fishermen's welfare. The potential of fisheries resources in Desa Pohon Batu requires further research for effective policy development. This study uses descriptive analytical methods to understand phenomena without making general conclusions. This approach allows for in-depth interpretation of collected data, providing holistic insights into the complexity of the phenomena under study. The combination of quantitative and qualitative methods yields a systematic and profound understanding of the relationships between variables and the narrative experiences of research participants. The study emphasizes the importance of understanding fishing methods and environmental awareness. Drift gillnets cause financial and ecological losses, while set gillnets improve operational efficiency. Fishermen's income is a critical factor in evaluating welfare, with most having low income due to minimal input production. This analysis is essential for developing policies supporting fishermen's welfare and economic resilience.